The Effect of Knowledge Management Capabilities on Project Management Success - Alghail, Adnan Ali; Liu, Yao; Cheng, Jack Kie; Alkawsi, Jamal (College of Business Management & Accounting, Universiti Tenaga Nasional, 2017)
Nowadays, the utilization of Knowledge Management (KM) is essential for modern organizations that are striving to fulfill their stakeholder's expectations, enhance business performance, and build a high reputation in global competitions by ensuring project s being delivered on time with planned budgets. However, there is a significant gap in the existing literature to address the core role or effect of knowledge management to the project management and to its practices. Therefore, it is pivotal for such orga nizations to explore and learn what KM capabilities are and what their impacts onto the organizations’ PM are . This paper aims to reveal the effect of KM capabilities, specifically the KM processes and the KM infrastructure. Which are considered as importa nt elements that enable the Project Management (PM) gaining and achieving a high organizational success. After explaining the theoretical concepts of KM, its capabilities as well as PM, it discovers and elaborates the effects that the KM capabilities may l ead in PM practices in organizations. It argues that establishing KM capabilities would contribute to the PM practices for the sake to have a recognized business functionality and advanced degree of the projects’ success. It implies that identifying the ef fect of KM capabilities in PM has the potential to enhance the organizational performance and achieve strategic goals in ongoing and future project activities